Health Inequities in Pediatric Trauma - Mark L. Kayton; Victoriya Staab; Brandon Stahl; Khea Tan; Larissa Russo; Meagan Verney; Margaret McGuire; Harpreet Pall (MDPI AG, 2023)
This review article highlights the disparities evident in pediatric trauma care in the United States. Social determinants of health play a significant role in key aspects of trauma care including access to care, gun violence, child abuse, head trauma, burn injuries, and orthopedic trauma. We review the recent literature as it relates to these topics. The findings from these recent studies emphasize the important principle that trauma care for children should be designed with a focus on equity for all children.